Introducing Second Language Acquisition: Perspectives and Practices - Alghazo, Sharif (Arab Journal of Applied Linguistics, 2018)
Introducing Second Language Acquisition: Perspectives and Practices By Kirsten M. Hummel Chichester, England: Wiley Blackwell, 2014 ISBN: 9780470658048 No of pages: 273 pages Reviewed by: Sharif Alghazo, University of Jordan